Teachers’ Perception of Parental Involvement of Primary Students: A Case Study in EYL Context - Refi Rizki Radian; Asri Siti Fatimah; Fera Sulastri (Siliwangi University, 2021)
Parental involvement of primary students is essential since it can contribute on their educational outcomes and development. Especially for learning English as a foreign language, parents play the prime source in developing their engagement and responsibility to have positive academic achievement in their early development. As well as their teachers, parents need to connect with school activities and be responsible in providing services to the children in education delivery. In this study, teachers’ perception of parental involvement in the process of learning English of primary students was investigated. It focuses on analyzing perception of three elementary school teachers who had experience in teaching English for more than 15 years. Data were collected by conducting semi-structured interviews and analyzed using thematic analysis (Braun Clarke, 2006). Descriptive case study was used as the research design because of the phenomenon that occurs in the involvement of parents in learning English to primary students. The results of this study involve three major themes. They are; 1) students' language development 2) teachers feeling, and 3) cooperation carried out by teachers and parents. As a conclusion, relationship between parents and teachers can have a positive impact. It opens valuable opportunities for children to develop language skills (especially English), and allows brilliant English achievements.